Japanese Men's Embodied Culinary and Eating Practices: Health, Bodyweight Control, and the Male Self. Issue 3 (October 2019) - Castro-Vázquez, Genaro
This article presents the outcomes of interview with a group of Japanese men to unveil how bodyweight control was connected to their embodied culinary and eating practices. Aged 24 years to 56 years, participants were from Tokyo and Osaka. Eight of the men identified themselves as "slim-muscular" and one as "beefy." Nine of them have been called "chubby" and two have been requested to lose weight. Grounded in symbolic interactionism, biopedagogy, gender, and emotion are the three axes used to present the analysis. Participants produced their own version of biopedagogy largely relying on the vegetablization of cooking to cope with healthism and sizeism entrenched in Japanese society. Some cooking and eating practices were underpinned by a pathological relation with food, others represented embodied masculinized practices connected to a recreational viewpoint of food and cooking. Cooking and eating delicious food represented an embodied "happy male self" and the meaning of "what makes life worth living."